Effects of Semaglutide on Cardiac Protein Expression and Cardiac Function of Obese Mice - Pan X; Yue L; Ban J; Ren L; Chen S (Dove Medical Press, 2022)
Xiaoyu Pan,1,2 Lin Yue,1,2 Jiangli Ban,2 Lin Ren,2 Shuchun Chen1,2 1Department of Internal Medicine, Hebei Medical University, Shijiazhuang, People's Republic of China; 2Department of Endocrinology, Hebei General Hospital, Shijiazhuang, People's Republic of ChinaCorrespondence: Shuchun Chen, Department of Endocrinology, Hebei General Hospital, Shijiazhuang, People's Republic of China, Tel +86 31185988406, Fax +86 31185988406, Email chenshuc2014@163.comPurpose: Using proteomics to study the effect of semaglutide on cardiac protein expression in obese mice. Assessment of the effect of semaglutide on cardiac function in obese mice.Materials and Methods: The mice were randomly divided into three groups: the control group (WC), the high-fat group (WF), and the high-fat diet with semaglutide intervention group (WS). Serum samples were collected, and lipids, blood glucose, inflammatory and oxidative stress markers, and cardiac ultrasound, were examined. The cardiac weight of each group of mice was measured, and pathological alterations were examined. Inflammation and oxidative stress levels in heart tissue were evaluated. The labeling coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS) platform was used to find differentially expressed proteins (DEPs) and screen for related pathways and key proteins in a proteomics study.Results: Semaglutide greatly alleviated obesity-induced lipid metabolism abnormalities, improved cardiac ventricular wall thickening, and significantly reduced myocardial collagen content in obese mice. Semaglutide significantly reduces obesity-induced inflammation and oxidative stress. There were 64 DEPs in the WF/WC group, with 39 upregulated proteins and 25 downregulated proteins. The WS/WC group, on the other hand, had 83 DEPs, including 57 upregulated and 26 downregulated proteins. Following functional analysis, DEPs were shown to be largely associated with lipid metabolism and peroxisomes. Apolipoprotein A-II, catalase, diazepam-binding inhibitor, paraoxonase-1, and hydroxysteroid 17-dehydrogenase-4 were all upregulated in the WF group but significantly downregulated in the WS group. A high-fat diet increases the expression of lipid synthesis and transport proteins while increasing inflammation and oxidative stress damage.Conclusion: Semaglutide decreases lipid synthesis alleviates inflammation and oxidative stress and prevents lipid peroxidation and cardiac impairment.Keywords: semaglutide, lipid metabolism, DEPs, obesity, inflammation, oxidative stress